A review of the pharmacokinetics of M3 muscarinic receptor antagonists used for the treatment of asthma. (1st February 2020) - Matera, Maria Gabriella; Rinaldi, Barbara; Berardo, Carmela; Rinaldi, Michele; Cazzola, Mario
ABSTRACT: Introduction : There is solid evidence that in patients with poorly controlled severe asthma despite the use of ICS and LABA, the addition of LAMAs, such as tiotropium, significantly increases the time to the first severe exacerbation and provides a modest but sustained bronchodilation. However, only a very limited number of pharmacokinetic studies with these agents have been performed in asthmatic patients. Areas covered : The pharmacokinetic profile of inhaled tiotropium, umeclidinium and glycopyrronium in healthy volunteers and that of inhaled tiotropium and umeclidinium in asthmatic patients have been reviewed. Expert opinion : In asthmatic patients, LAMAs are rapidly absorbed into the systemic compartment and demonstrate bi-exponential elimination (rapidly declining plasma concentrations followed by slow apparent terminal elimination). Apparently, the severity of asthma does not change the pharmacokinetics of LAMAs. The limited information available is focused on the plasma pharmacokinetic profile of these drugs and, consequently, although suitable for establishing a systemic safety profile, it does not tell us much about possible therapeutic efficacy of LAMAs in asthmatics because quantification of systemic plasma values is neither at the airways, which are their site of action nor representative of their transport to this site.